Persepsi Tamu OTA Terhadap Dimensi Pelayanan Tangible, Resposiveness, Realibility, Empathy, Assurance di TC Damhil dalam Meningkatkan Tingkat Hunian Kamar - Poppy Arnold Kadir; Meilinda Lestari Modjo (Ideas Publishing, 2021)
This study aims to determine the perception of OTA (Online Travel Agent) guests on the dimensions of tangible, responsiveness, realibility, empathy, assurance services at TC Damhil UNG (Gorontalo State University), to determine the room occupancy rate at TC Damhil, and to determine the efforts made management to improve the Service Dimensions Tangible, Responsiveness, Realibility, Empathy, Assurance at TC Damhil UNG in increasing the room occupancy rate. This research data collection through observation, interviews, and literature study, the type of qualitative research. Primary and secondary data are the data sources used in this study. In accordance with the results of the study, it shows that the perception of OTA guests towards the assessment of the service dimensions, both tangible, empathy, realibility, irresponsiveness, and assurance on room occupancy rates is very good on 4 dimensions, namely empathy, realibility, responsiveness, and assurance. As for the tangible dimension, it still needs to be improved, especially regarding the improvement of physical facilities owned by TC Damhil. HR Reliable and professional human resources are a strength for TC Damhil in improving the quality of services in the accommodation sector in Gorontalo because the State University of Gorontalo has alumni who have the ability and knowledge in the hospitality sector. OTA Online Travel Agent is a digital marketing that is very effective in increasing the room occupancy rate and becomes a reference for the manager to be able to fix what is a deficiency for guests. The room occupancy rate is an indicator of the success of the management in the accommodation sector. To be able to increase the room occupancy rate, the quality of service provided by TC Damhil must be able to meet the needs and desires of guests. Penelitian ini bertujuan untuk mengetahui persepsi tamu OTA (Online Travel Agent) pada dimensi pelayanan tangible, responsiveness, realibility, empathy, assurance di TC Damhil UNG (Universitas Negeri Gorontalo), untuk mengetahui tingkat hunian kamar di TC Damhil, dan untuk mengetahui upaya yang dilakukan manajemen dalam meningkatkan Dimensi Pelayanan Tangible, Responsiveness, Realibility, Empathy, Assurance di TC Damhil UNG dalam meningkatkan tingkat hunian kamar. Pengumpulan data penelitian ini melalui observasi, wawancara, dan studi pustaka, jenis penelitian kualitatif. Data primer dan sekunder merupakan sumber data yang digunakan pada penelitian ini. Sesuai dengan hasil penelitian, menunjukkan persepsi tamu OTA terhadap penilaian pada dimensi pelayanan baik tangible, empathy, realibility, responsiveness, dan assurance terhadap tingkat hunian kamar sudah sangat baik pada 4 dimensi yakni empathy, realibility, responsiveness, dan assurance. Sedangkan untuk dimensi tangible masih perlu diperbaiki terutama mengenai perbaikan fasilitas fisik yang dimiliki oleh TC Damhil. Sumber daya manusia yang handal dan profesional merupakan kekuatan bagi TC Damhil dalam meningkatkan kualitas pelayanan di bidang akomodasi di Gorontalo karena Universitas Negeri Gorontalo memiliki alumni yang memiliki kemampuan dan pengetahuan di bidang hospitality. OTA merupakan digital marketing yang sangat efektif meningkatkan tingkat hunian kamar dan menjadi rujukan bagi pihak pengelola untuk dapat memperbaiki apa yang menjadi kekurangan bagi tamu. Tingkat hunian kamar merupakan indikator penilaian keberhasilan dalam pengelolaan di bidang akomodasi. Untuk dapat meningkatkan tingkat hunian kamar, maka kualitas pelayanan yang diberikan oleh TC Damhil harus dapat memenuhi kebutuhan dan keinginan tamu.